(untitled) (Molecular Medicine Communications, 2023)
Variations in the melanocortin 4 receptor (MC4R) are most commonly associated with serious early-stage monogenic obesity. The valosin-containing protein (VCP) gene, also referred to as p97, produces the ubiquitous, crucial, and multifunctional protein VCP, involved in a wide range of cellular processes, including endoplasmic reticulum-associated degradation (ERAD), degradation of lysosomal protein, and degradation of the proteasome-mediated protein. In the present study, we investigated two Pakistani families enrolled from Sibi, Pakistan, for variation in MC4R and VCP genes. Clinical symptoms involved obesity, hyperphagia, and diabetes in Family 1. Obesity with autism spectrum disorder (ASD), hyperphagia, diabetes, seizure, gastrointestinal, and sleep disorders were found in Family 2. Additionally, blood samples were collected and DNA extraction was performed. Subsequent molecular analysis was conducted to identify mutations. Clinical and genetic results were analyzed, and the segregation of MC4R and VCP gene variants in the families helped to make the diagnosis of the disease. For the identification of variations, we conducted whole exome sequencing (WES) and confirmed the findings through target sequencing. We divulged two previously reported heterozygous missense variations. Notably, WES revealed variants (c.307G>A, rs2229616) in the MC4R and (c.1360-35A>G, rs2258240) in the VCP genes in both families separately. The chromatogram illustrated homozygous unaffected siblings and parents, as well as heterozygous individuals with the disease. Both families segregate with the obesity disorder in an autosomal dominant manner. In Family 1, the change from ‘G’ to ‘A’ in the MC4R gene depicts the mutant allele ‘A’ segregating dominantly from one generation to another. Similarly, the change from ‘A’ to ‘G’ in the VCP gene illustrates the mutant allele ‘G’ segregating dominantly in Family 2.